The Opinions Of Grammarians Described As Al-Hudaq In Arabic Grammar: The Chapter On Verbs As A Model/ آراء النحويّين الموصوفين بـالحُذّاق في النحو العربي، باب الأفعال أنموذجا - Ahmed Aref Jumaa Al-Kubaisi; Rafi Khalaf Jassim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The study aims to collect distinguished grammatical opinions attributed to the “Al-Ḥuḏāq,” a term referring to groups of senior grammarians in classical works, as seen in expressions such as “the expert grammarians” and “clarified by the Al-Ḥuḏāq.” The grammarians themselves frequently transmitted opinions using this designation; for example, al-Nahhās says: “the expert grammarians do not say and (لها) meaning (عليها).” The purpose of the research is to gather these opinions, specifically those related to Arabic verbs, to study and analyze them, compare them with other viewpoints, and identify the names of these “Al-Ḥuḏāq.” The researcher relied on surveying disputed issues in classical texts and on indices of books on grammatical schools. The study revealed the identities of the grammarians referred to as “Al-Ḥuḏāq” in each issue and clarified that the term “Al-Ḥuḏāq”—if it can be considered a technical term—entails two aspects: first, grammarians do not label a school as the “Al-Ḥuḏāq” school without generally intending to give it preference; second, describing a particular group as “Al-Ḥuḏāq” serves as a form of praise for the grammarians themselves, highlighting their reliability and authority, since ḥadhāqah denotes skill and mastery. Moreover, these issues affect the teaching of Arabic to non-native speakers.